2017
DOI: 10.2166/wh.2017.255
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of swimming pool water by recreational swimmers

Abstract: The volume of water ingested by swimmers while swimming is of great interest to individuals who develop risk assessments using quantitative microbial risk assessment or epidemiological approaches. We have used chloroisocyanurate disinfected swimming pool waters to determine the amount of water swallowed by swimmers during swimming activity. The chloroisocyanurate, which is in equilibrium with chlorine and cyanuric acid in the pool water, provides a biomarker, cyanuric acid, that once swallowed passes through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 22 publications
0
42
0
2
Order By: Relevance
“…Sample volumes per minute (mL/min) from Dufour et al (2017 ( 34 )) and Evans et al (2006) The volume of water swallowed during the swimming pool study was divided by the self-reported total time spent in the pool, to yield an estimated rate of water swallowed (. Sampling was conditional on age and sex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample volumes per minute (mL/min) from Dufour et al (2017 ( 34 )) and Evans et al (2006) The volume of water swallowed during the swimming pool study was divided by the self-reported total time spent in the pool, to yield an estimated rate of water swallowed (. Sampling was conditional on age and sex.…”
Section: Methodsmentioning
confidence: 99%
“…This simulation was conducted for each age group using all participants, and for males and females separately, since evidence suggests males may swallow a greater volume compared to females ( 26 , 34 , 36 – 38 ). The simulation was also conducted separately based on beach water type (freshwater and marine), since behavior was expected to differ at different types of beaches ( 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…From the standpoint of broader application of the methodology presented, the results of a study of the volume of ingested water by a large group of volunteers from a broad range of age groups during recreational swimming activities, using the methodology described for the first time here, are presented in Refs. [12,46], which represent pilot-scale and full-scale studies, respectively. An additional broader application is that while the development of the methodology discussed was predicated on ingestion of water during swimming, the results may also have implications for other studies of ingestion of cyanuric acid through other means as has occurred, perhaps most notably through contamination or adulteration of animal feed or infant formula in the United States and China, respectively [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used biomarker for long term exposure in pregnancy is urinary trichloroacetic acid (Costet et al, 2012;Smith et al, 2013). However, this marker represents ingestion of chlorinated DBPs but not inhaled or absorbed DBPs through the skin as would occur from swimming pools (Dufour et al, 2017). Blood, urine or exhaled breath trihalomethanes only capture short term exposures (inhalation and dermal absorption) and in some cases chronic drinking water exposure (Backer et al, 2008;Rivera-Núñez et al, 2012;P.…”
Section: Discussionmentioning
confidence: 99%
“…Swimming, as a physical activity, has benefits for cardiovascular health, fitness, and respiratory function. Swimming pools also contain microbes and potential toxicants such as disinfection by-products (DBP) (De Filippis et al, 2017;Dufour et al, 2017;Ekowati et al, 2017;Manasfi et al, 2017). DBPs are a complex mixture of organic chemicals formed from reactions of the brominated or chlorinated compounds used in pool disinfection with organic matter such as microbes (Manasfi et al, 2017;Richardson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%